STORYBOOK DIGITAL INTERAKTIF BERMUATAN KEARIFAN LOKAL KISAH MAYADENAWA BERBASIS PENDEKATAN DEEP LEARNING. - Ida Bagus Yoga Swadnyana; I Wayan Sujana; Anak Agung Ratih Prabaswari; I Komang Agun Diantara; Ni Luh Putu Girad Giriastana (STKIP Subang, 2026)
This study aimed to develop an interactive digital storybook based on the local wisdom of the Mayadenawa folklore using a deep learning approach, as well as to examine its feasibility and practicality in elementary school learning. The research employed a Research and Development (R&D) method using the Borg and Gall model, which consists of ten systematic stages from needs analysis to product dissemination. The participants involved experts in development, instructional design, content, and media, as well as third-grade elementary school students for product trials. Data were collected through questionnaires and analyzed using descriptive quantitative techniques with a Likert scale and Benchmark Reference Assessment (PAP). The results show that the developed media is highly valid, as indicated by expert validation scores of 94% (development), 88.5% (instructional design), 90.6% (content), and 87.1% (media). In addition, the practicality test reaches 95% in both individual and small group trials, indicating very high practicality and positive student responses. These findings indicate that the interactive digital storybook is valid and practical for use in learning. Furthermore, the integration of a deep learning approach enables students to not only understand the story at a surface level but also analyze and relate its values to their daily lives, fostering critical and reflective thinking. Therefore, this media serves as an innovative and meaningful learning tool that enhances student engagement while supporting the preservation of local cultural values.